Loss of PTEN expression and AKT activation in HER2-positive breast carcinomas - Francini de Mattos Lima Lin; Carlos Eduardo Bacchi; Edmund Chada Baracat; Filomena Marino Carvalho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE: To examine the expression of AKT and PTEN in a series of HER2-positive primary invasive breast tumors using immunohistochemistry, and to associate these expression profiles with classic pathologic features such as tumor grade, hormone receptor expression, lymphatic vascular invasion, and proliferation.METHODS: A total of 104 HER2-positive breast carcinoma specimens were prepared in tissue microarrays blocks for immunohistochemical detection of PTEN and phosphorylated AKT (pAKT). Original histologic sections were reviewed to assess pathological features, including HER2 status and Ki-67 index values. The associations between categorical and numeric variables were identified using Pearson's chi-square test and the Mann-Whitney, respectively.RESULTS: Co-expression of pAKT and PTEN was presented in 59 (56.7%) cases. Reduced levels of PTEN expression were detected in 20 (19.2%) cases, and these 20 tumors had a lower Ki-67 index value. In contrast, tumors positive for pAKT expression [71 (68.3%)] were associated with a higher Ki-67 index value.CONCLUSION: A role for AKT in the proliferation of HER2-positive breast cancers was confirmed. However, immunohistochemical detection of PTEN expression did not correlate with an inhibition of cellular proliferation or control of AKT phosphorylation, suggesting other pathways in these mechanisms of control.